X-ray phase-contrast imaging for laser-induced shock waves. (4th March 2019) - Antonelli, L.; Barbato, F.; Mancelli, D.; Trela, J.; Zeraouli, G.; Boutoux, G.; Neumayer, P.; Atzeni, S.; Schiavi, A.; Volpe, L.; Bagnoud, V.; Brabetz, C.; et al.
Abstract: X-ray phase-contrast imaging (XPCI) is a versatile technique with applications in many fields, including fundamental physics, biology and medicine. Where X-ray absorption radiography requires high density ratios for effective imaging, the image contrast for XPCI is a function of the density gradient. In this letter, we apply XPCI to the study of laser-driven shock waves. Our experiment was conducted at the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) at GSI. Two laser beams were used: one to launch a shock wave and the other to generate an X-ray source for phase-contrast imaging. Our results suggest that this technique is suitable for the study of warm dense matter (WDM), inertial confinement fusion (ICF) and laboratory astrophysics.